A balanced time perspective: Is it an exercise in empiricism, and does it relate meaningfully to health and well‐being outcomes?. (11th September 2018) - McKay, Michael. T.; Worrell, Frank. C.; Zivkovic, Urška; Temple, Elizabeth; Mello, Zena. R.; Musil, Bojan; Cole, Jon C.; Andretta, James R.; Perry, John L.
Abstract : Time perspective research assesses the degree to which thoughts and feelings about the past, present and future influence behaviour, and a balanced time perspective profile has been posited as being ideal. Although this area of research has seen a move towards person‐centred analyses, using either cluster analyses or a deviation from balanced time perspective (DBTP) approach, there are a number of theoretical and methodological issues that must be addressed. Using data from diverse samples in four countries, the present study used both cluster analyses and the DBTP approach to assess how cluster membership and DBTP scores related to a range of health and well‐being outcomes. As in previous studies, a balanced profile only emerged once in cluster analyses, and positive‐oriented profiles were associated with optimal outcomes. The study also found evidence of a relationship between DBTP scores and scores on well‐being indicators. However, results gained after manipulating the DBTP equation in two different ways again indicated that higher than expected positive past and present or past and future scores were responsible for the positive outcomes. As such, these findings raise concerns regarding the use of the DBTP construct within clinical settings.